Ukaz ermosam - Orthodox Eastern Church
Calendar in rubric form listing appropriate hymns for daily services.
Collection material in Church Slavic.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Orthodox Eastern Church -- Hymns; Hymns, Church Slavic